2009
DOI: 10.1007/s00381-009-0812-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-related peridural hyperemia in craniosynostotic rabbits

Abstract: Objective Craniosynostosis is the premature fusion of the calvarial sutures and is associated with aesthetic impairment and secondary damage to brain growth. Associated neurological injuries can result from increased intracranial pressure (ICP) and abnormal cerebral blood flow (CBF). Arterial spin-labeling (ASL) MRI was used to assess regional CBF in developing rabbits with early-onset coronal suture synostosis (EOCS) and age-matched wild-type controls (WT). Methods Rabbits were subjected to ASL MRI at or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, we demonstrated that early surgical correction mitigated adverse changes in the white matter tissue microstructure, with no statistically significant differences found in quantitative DTI parameters between surgically corrected and age-matched control animals. This study adds new evidence to the existing sequelae of craniosynostosis in the rabbit model, including decreased brain growth 5 and intracranial volume, 6 surface cortex blood flow anomalies, 16 and hyperactivity with early reflexive behavior in the early stages of life. 21 …”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, we demonstrated that early surgical correction mitigated adverse changes in the white matter tissue microstructure, with no statistically significant differences found in quantitative DTI parameters between surgically corrected and age-matched control animals. This study adds new evidence to the existing sequelae of craniosynostosis in the rabbit model, including decreased brain growth 5 and intracranial volume, 6 surface cortex blood flow anomalies, 16 and hyperactivity with early reflexive behavior in the early stages of life. 21 …”
Section: Discussionmentioning
confidence: 74%
“…Pioneer work by Virchow showed that the primary defect lies within the suture that is later translated to the cranial base by an unknown mechanism [12]. Moss then postulates that the cranial base is the source of the primary defect, which translates its effects on the suture through the dura mater [13].…”
Section: Discussionmentioning
confidence: 99%
“…This study used a breeding colony of New Zealand white rabbits with naturally occurring coronal suture synostosis [ 15 , 21 25 ]. All rabbits were born and maintained in the vivarium at the Department of Anthropology, University of Pittsburgh and housed in stainless steel cages with access to food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…CBF was studied in EOCS rabbits at 10, 25 and 42 days of age using ASL-MRI. A previous study from our group revealed CBF to be similar between wild-type (WT) and EOCS subjects, with the exception of the superficial cortex surfaces in EOCS rabbits at 25 days of age [ 25 ]. A two-fold increase in superficial cortex CBF at 25 days of age was noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation